Risks and predicting factors of bleeding complications in hepatitis B virus-related acute-on-chronic liver failure - Guo, Hong-ying; Zhang, Zheng-guo; Zhang, Yu-yi; Mei, Xue; Liu, Yu; Wang, Jie-fei; Qian, Zhi-ping; Yuan, Wei (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To provide supporting evidence for prevention and prognostic evaluation of bleeding complications in the early stage by exploring the risk and predicting factors in patients with acute-on-chronic liver failure (ACLF).Materials and Methods: A total of 101 hospitalized patients with ACLF were retrospectively included from January 1, 2014 to December 31, 2015. The patients were divided into bleeding (n=38) and nonbleeding groups (n=63). Demographic data and laboratory tests were recorded and compared between the two groups. The incidence, risk factors, and prognosis of bleeding complications among patients with ACLF were investigated.Results: A total of 38 cases (37.62%) had bleeding complications: 26 (25.74%) were spontaneous and 12 (11.88%) were postprocedural. Patients with bleeding complications had lower platelet (p=0.008), fibrinogen (p<0.001), factor V (p=0.001), and factor VII (p=0.026) levels; higher serum creatinine levels (p=0.004); and a higher proportion of cirrhosis (p=0.013). Logistic regression analysis showed that cirrhosis (odds ratio=3.251, p=0.046), fibrinogen level (odds ratio=0.352, p=0.007), and factor VII level (odds ratio=0.951, p=0.011) contributed to the development of bleeding complications. A subgroup analysis of invasive manipulation-induced bleeding complications showed lower levels of factors V (p=0.018) and VII (p=0.021) in the postprocedural bleeding group. Follow-up studies showed that the nonbleeding group had a higher survival rate than the bleeding group at day 90 (73.33% versus 51.85%, p=0.040).Conclusion: Liver cirrhosis, lower levels of fibrinogen, and major coagulation factor activity in patients with ACLF were associated with an elevated risk of bleeding events during hospitalization, which further impaired the 90-day survival rate.